Safety of the tau-directed monoclonal antibody BIIB092 in progressive supranuclear palsy: a randomised, placebo-controlled, multiple ascending dose phase 1b trial. Issue 6 (June 2019) - Boxer, Adam L; Qureshi, Irfan; Ahlijanian, Michael; Grundman, Michael; Golbe, Lawrence I; Litvan, Irene; Honig, Lawrence S; Tuite, Paul; McFarland, Nikolaus R; O'Suilleabhain, Padraig; Xie, Tao; Tirucherai, Giridhar S; et al.
Summary: Background: Progressive supranuclear palsy is a rare neurodegenerative disease associated with dysfunctional tau protein. BIIB092 is a humanised monoclonal antibody that binds to N-terminal tau and is thus being assessed as a potential novel treatment for progressive supranuclear palsy. We aimed to investigate the safety and tolerability of BIIB092 in individuals with progressive supranuclear palsy. Methods: This 12-week, double-blind, randomised, placebo-controlled, multiple ascending dose, phase 1b trial was done at 13 outpatient sites in the USA. Participants aged 41–86 years with probable or possible progressive supranuclear palsy with a score of 20 or greater on the Mini-Mental State Examination (MMSE) were enrolled. Three BIIB092 dose escalation cohorts (150 mg, 700 mg, or 2100 mg; eight participants per cohort) were tested sequentially. For each dose cohort, the first two participants were randomly assigned by a computer-generated scheme to receive either BIIB092 or placebo intravenously every 4 weeks for 57 days. After 2 days, the six remaining participants in each cohort were randomly assigned (5:1) to receive BIIB092 or placebo for 57 days. An additional expansion panel of 24 patients was randomly assigned (3:1) to receive 2100 mg or placebo every 4 weeks for 57 days. All participants were followed up to day 85. The primary outcome was safety, which was analysed in the treated population (all enrolled participants who received at least one dose of the study drug). This trial is registered with ClinicalTrials.gov, NCT02460094 . Findings: Between Oct 2, 2015, and Oct 19, 2016, 48 participants were enrolled and randomly assigned to the BIIB092 (n=36) and placebo (n=12) groups. No apparent demographic differences were observed between the two groups at baseline. All 48 participants completed the treatment phase of the study. Adverse events were generally mild to moderate in severity; the most common in the placebo and BIIB092 groups were falls (in two [17%] of 12 patients and in ten [28%] of 36 patients), urinary tract infections (in one [8%] of 12 and in six [17%] of 36), contusions (in one [8%] of 12 and in five [14%] of 36), and headaches (in none and in five [14%] of 36). Four serious adverse events resulting in admission to hospital were reported in three participants who received BIIB092 2100 mg: two severe adverse events of urinary tract infection, one severe adverse event of change in mental status, and one moderate adverse event of aspiration pneumonia. None was considered to be related to the study drug, all were resolved, and no deaths were reported. Interpretation: Repeated administration of the anti-tau monoclonal antibody BIIB092, at doses of up to 2100 mg, appears to be well tolerated in participants with progressive supranuclear palsy. Results of this phase 1b trial have informed the design of the ongoing phase 2 PASSPORT (NCT03068468 ) study to examine the efficacy and safety of BIIB092. Funding: Bristol-Myers Squibb, Biogen.